Synthesis and characterization of polyoxometalate-based silver(i) phenylethynide compounds with antibacterial and antifungal activities. Issue 25 (13th June 2017) - Hu, Ting; Li, Yu-Hang; Kuang, Xiao-Fei; Lu, Can-Zhong
Abstract : Six new silver-phenylethynide double salts with the crystal structures of a coordinated silver column (1, 6 ), an infinite silver chain (2, 3 ) and a discrete molecule (4, 5 ) have been synthesized and structurally characterized. The pure phases of1–5 are obtained and found to have antibacterial and antifungal properties. Abstract : Six new silver-phenylethynide compounds, namely, [(AgCCPh)4 (AgCF3 SO3 )(DMSO)2 ] (1 ), [(AgCCPh)(Ag3 PW12 O40 )(DMSO)8 ] (2 ), [(AgCCPh)(Ag3 PMo12 O40 )(DMSO)8 ] (3 ), [(AgCCPh)(Ag4 SiW12 O40 )(DMSO)10 ] (4 ), [(AgCCPh)8 (Ag4 SiW12 O40 )(DMSO)10 ] (5 ), and [(AgCCPh)16 (Ag3 PW12 O40 )(DMSO)8 (H2 O)2 ] (6 ), have been synthesized and structurally characterized by X-ray crystallography. These compounds exhibit a coordinated silver column structure with OTf − /POM anions serving as counter-anions (1, 6 ), an infinite chain structure based on the coordinated Ag4 aggregates and POM anions (2, 3 ) and a discrete molecular structure containing coordinated silver aggregates and POM anions (4, 5 ), respectively. The pure phases of1–5 are obtained and identified. The antibacterial/antifungal activities of1–5 are screened by the disk diffusion method against the bacteria strains Bacillus pumilus, Bacillus subtilis, Staphylococcus aureus and Escherichia coli and the fungi strains Aspergillus niger and Canidia albicans, and the MIC/MBC values are also measured. The cytotoxicity and biological toxicity test results showed that these compounds have low toxicity in both cells and animals.